Analisis Pengaruh Ikatan Emosi dan Kualitas Pelayanan Melalui Kepuasan Terhadap Loyalitas Wisatawan Di Wisata Pulau Poncan Gadang, Kabupaten Tapanuli Tengah-Sumatera Utara - Siregar, Mira Yosefa (TOBA: Journal of Tourism, Hospitality, and Destination, 2022)
This study aims to determine the analyze and the effect of  emotional bonding and service quality through satisfaction on tourist loyalty at the Poncan Gadang Island tourist attraction, Central Tapanuli Regency. The population in this study were all people who came to travel to Poncan Gadang Island, Kabupaten Tapanuli-Tengah. In this study, data were collected through observation, interviews and documentation of 32 informants obtained using stratified random sampling technique. The type of data in this study is qualitative data analysis, qualitative descriptive method. The results show that Emotional Bonding (X1) and Service Quality (X2), through Satisfaction (Z), simultaneously have a positive effect on tourist loyalty (Y) in Poncan Gadang Island tourism, Kabupaten Tapanuli-Tengah. Therefore, there is a need for marketing promotions such as opening a bazaar stand, having a link or website specifically for Sibolga City tourism, through massive social media so that people know and come to visit Poncan Gadang Island,  Tapanuli-Tengah, North Sumatra.